Detection and molecular identification of citrus stem rot disease in Bali Province - Wirya, Gusti Ngurah Alit Susanta; Agung, I Dewa Agung Putra; Sudiarta, I Putu (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
One major disease of citrus is basal stem rot which may cause significant constraint on citrus production in Indonesia. Basically the diseasecan be caused by fungi Phytophthora spp., Diplodia sp., and Botryodiplodia theobromae or Lasiodiplodia theobromae. The purpose of this study wasto provide information on the main pathogens and characterization of BPB disease, especially in citrus in Bali, which ultimately leads to early warning for protection against BPB disease and enriches academic evidence about pre-existing BPB disease.The method used is observation andisolation, pathogenicity test, and in vitro inhibitory test. Research activities include (1) sampling, (2) isolation of pathogens from symptomatic citrusplants, (3) test of pathogenicity, (4) identification of pathogen morphology and molecular, (5) DNA amplification, (6) DNA electrophoresis (7) analysis of DNA sequences. The results of this research successfully identified Lasiodiplodia theobromae, as a pathogen of citrus stem rot disease in Bali Province.